Thông tin khoa học (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
International Conference "30 Years of Doi Moi: Success, Lessons and Prospects" On 8th October 2016, the International Conference "30 Years of Doi Moi: Success, Lessons and Prospects" was organised by VNU University of Social Sciences and Humanities, Hanoi (VNU-USSH), supported by Konrad Adenauer (KAS), Germany. Many researchers participated in this event came from  Germany and Vietnam, such as Associate Prof Nguyen Hong Quan, Institute of National Defense Strategies, Ministry of National Defense, Mr Vu Khoan-Former Deputy Prime Minister of Vietnam, Dr Stefan Kaufmann, member of Geman's Parliament; Prof.Dr Martin Grossheim (Passau University, Germany), Mr Peeter Girke, Head  Representative of KAS in Vietnam, Prof Pham Quang Minh, Rector of VNU-USSH, and other researchers and students from Faculty of International Studies, VNU-USSH.The conference consists of 5 sections with keynote speakers (Doi Moi as the key for Germany and Vietnam Relationship), Doi Moi from comparison perspectives (international integration of Vietnam: Comparison with regional countries, Unended history: Doi Moi in the view of comparison research", Doi Moi in terms of economics, national defense and diplomacy (International cooperation and military in foreign affairs: 30 years of retrospect; Doi Moi in classroom: Vietnam history in Vietnamese historical textbooks; 30 years of Vietnam-US relations: from enemy to comprehensive partnership; Outcomes of multilateral foreign policy: the confirmation of Vietnam status in the international arena);  Doi Moi in culture, society and education (30 years of Doi Moi in Cuture; Evaluating the legal impacts: the renovation in legal making in Vietnan; human development in Vietnam after 30 years of Doi Moi:  Achievements and limitations; Evaluative model on higher education quality: an innovation of Vietnam education system); Challenges and opportunities of Doi Moi (30 years of Doi Moi: toward the second Doi Moi with intensive speed and wide area; Cultural Renew in Vietnam: implications from achievements and future development directions). (Tran Van Kham) International Conference: "ASEAN Journalism: Comparative perspectives Under support by KAS (Germany), VNU University of Social Sciences and Humanities, Hanoi organised the international conference about Asean Journalism: comparative perspectives on 19th Oct 2016. Prof Pham Quang Minh, Rector of VNU-USSH, Mr Peter Girke (head of KAS in Vietnam), Mr Ho Quang Loi (Vice President of Vietnam Journalist Association) attended and made speeches at the conferences. There were many researchers and practitioners from Vietnam, Germany, Thailan also attended and presented papers in one day conference.The Conference consists of two sections with topics of: Asean journalism: the similarities and differences; challenges and opportunities for cooperation; overview of Asean journalism: significant milestones and development periods; political directions and trends in Asean journalism; role of journalism in the development of Asean community; challenges for Asean journalism in the digital age; efforts of Asean journalism on communicating the Asean: case study of the Journal of "World and Vietnam"; journalism cooperation among regional countries in the mission of Asean to 2025; television products for multi country audiences and model of Asean Children Festival, etc.(Tran Van Kham) International Conference "The archive sources on Vietnam in the modern history: Value and accessibility" VNU University of Social Sciences and Humanities, Hanoi in the coordination with Aix-Marseille, France organized the International Conference on " The archive sources on Vietnam in the modern history: value and accessibility" on 27th October 2016. This conference attracts a wide range of participants from Vietnam, America, German, Japan and France to share and update the research work about the forms of archive sources, its roles on doing social research related to Vietnam word wide.More than 30 papers presented 2 panels with 7 sections. The first panel, document sources about Vietnamese history and politics in modern period, consists of papers in Western sources about Vietnamese history: current status and prospects; archive sources about history of Vietnam in the French colonial period: the trap of diversity; categories related to Ho Chi Minh in complex fonts of Slotfom; relics of archives and evidence: historical sources for doing current historical research in the Northern of Vietnam… And the second one, about the Vietnamese society and economics in modern time, covers papers in titles of: Introduction archive blocks of Japanese trading companies in Vietnam in premodern and modern time; historical sources about Vietnamese migration: case of Japanese (1880-1950); documents about the association operations during the French colonial period in the national archive centers of Vietnam and France, etc.It is significant conference to look for the value of the archives sources and the worthy event for 25th year anniversary establishment of the Faculty of Archive and Office Managements, VNU-USSH, and the milestone of 50th year on training the archive program in Vietnam.(Tran Van Kham)